THE VERSATILITY OF EXCIMER LASER IN ORAL LICHEN PLANUS - M.D.S, DR. SANKAR NARAYANAN R; A.S, DR. SARIKA; MURALIDHARAN, AISHWARIYA RAO (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Oral lichen planus (OLP) is a chronic,immune mediated inflammatory condition primarily composed of T cells which commonly affects the muco-cutaneous parts of the body. Current treatment strategies aim to manage the disease morbidity through lifestyle modifications and pharmacological interventions. However, OLP often shows frequent relapses and also develop potential adverse effects due to the long term use of steroids which are the first-line medication for OLP.Consequently, alternative management approaches are required to address the heterogeneous nature of this condition. The 308-nm excimer laser has demonstrated efficacy in the treatment of various inflammatory and pigmented lesions in dermatology. This specific 308-nm monochromatic laser has been shown to be highly effective which directly target the inflammatory components of OLP lesion thereby providing symptomatic relief in patients. This study aims to review the application of excimer laser for the management of oral lichen planus.